Career adaptability and university-to-work transition: effects on graduates' employment status - Monteiro, Sílvia (2019)
Purpose: In a socioeconomic context that is undergoing continuous change, career adaptability emerges as a central construct for understanding the employability of graduates. The purpose of this paper is twofold: first, to analyze intra-individual differences in career adaptability among graduates between the end of graduation (time 1) and integration into the labor market 18 months later (time 2); and second, to analyze the effect of career adaptability on graduates’ employment status 18 months after completing graduation. Design/methodology/approach: A sample of 183 graduates in four different study fields (Economics, Engineering, Social Sciences and Humanities and Law) completed the Career Adapt-Abilities Scale at two different points in time: when they graduated and 18 months after graduation. To assess intra-individual differences over time and the effect of career adaptability on graduates’ employment status, a repeated measures design was used. Findings: The obtained results confirmed a positive association of the four dimensions of career adaptability, with higher scores for the group of employed graduates, in the two measurement times. No statistical differences emerged within personal variables. Practical implications: This study evidences the relation of career adaptability and employability and demonstrates that it is possible to identify those students who are more vulnerable in terms of career adaptability resources before university-to-work transition and, on this basis, to outline specific interventions to promote their employability. Originality/value: By adopting a design with two repeated measures of career adaptability, this study offers new insights about the specific role of adaptability in a university-to-work transition period.